Recognizing Plant Defense Priming. (October 2016) - Martinez-Medina, Ainhoa; Flors, Victor; Heil, Martin; Mauch-Mani, Brigitte; Pieterse, Corné M.J; Pozo, Maria J.; Ton, Jurriaan; van Dam, Nicole M.; Conrath, Uwe
Abstract : Defense priming conditions diverse plant species for the superinduction of defense, often resulting in enhanced pest and disease resistance and abiotic stress tolerance. Here, we propose a guideline that might assist the plant research community in a consistent assessment of defense priming in plants.